GESTÃO DE RECURSOS HÍDRICOS POR COMITÊS DE BACIAS HIDROGRÁFICAS: LIMITES E DESAFIOS NA IMPLEMENTAÇÃO DO MODELO NOS ESTADOS DO NORDESTE - Morais, Jose Luciano Mendonca (2012)
This work was developed with the aim of analyzing the restrictive factors and drivers in implementing the current model of water management by river basin committees in the northeastern states. The work raised and described the factors influencing the implementation process of this management policy, highlighting the technical, political and financial, factors defined by Gutiérrez (2006) as essential for the sustainability of watershed committees. In this study we surveyed fourteen basin committees existing in the northeastern states. In research, quantitative and qualitative approach was used as a research strategy, the method of multiple case studies and methodological procedures were reviewing the literature, questionnaires, exploratory interviews, and finally the analysis and comparison of data secondary and primary. The conclusions reached indicate that almost all the committees have not considered financial sustainability, the only exception is in the state of Ceará already started the process of charging for water use, but the committees of this state do not participate in planning the use of water. In reality the vast majority of committees have not yet started charging for water use, does not have water agency, does fundraising from other sources, with guaranteed operation, with many restrictions by state governments through the agencies responsible the implementation of water policy. Finally the paper points out its limitations and suggests promising new fields for research.